2009
DOI: 10.1038/nature08287
|View full text |Cite
|
Sign up to set email alerts
|

A p53-mediated DNA damage response limits reprogramming to ensure iPS cell genomic integrity

Abstract: The reprogramming of differentiated cells to pluripotent cells (induced pluripotent stem (iPS) cells) is known to be an inefficient process. We recently reported that cells with short telomeres cannot be reprogrammed to iPS cells despite their normal proliferation rates, probably reflecting the existence of 'reprogramming barriers' that abort the reprogramming of cells with uncapped telomeres. Here we show that p53 (also known as Trp53 in mice and TP53 in humans) is critically involved in preventing the reprog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
849
4
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 938 publications
(912 citation statements)
references
References 29 publications
47
849
4
7
Order By: Relevance
“…Only a few cells can overcome this barrier and become iPSCs. A number of studies demonstrated that when key components (such as p53 and p21) of the DNA damage pathway were deleted, the percentage of iPS cell generation significantly increased (Zhao et al, 2008a;Banito et al, 2009;Hong et al, 2009;Kawamura et al, 2009;Li et al, 2009;Marión et al, 2009;Utikal et al, 2009b). Suppression of the p53 pathway may compromise a cell's genome stability.…”
Section: Overcoming the Dna Damage Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Only a few cells can overcome this barrier and become iPSCs. A number of studies demonstrated that when key components (such as p53 and p21) of the DNA damage pathway were deleted, the percentage of iPS cell generation significantly increased (Zhao et al, 2008a;Banito et al, 2009;Hong et al, 2009;Kawamura et al, 2009;Li et al, 2009;Marión et al, 2009;Utikal et al, 2009b). Suppression of the p53 pathway may compromise a cell's genome stability.…”
Section: Overcoming the Dna Damage Responsementioning
confidence: 99%
“…As the DNA damage pathway poses a major barrier towards regaining pluripotency (Zhao et al, 2008b;Banito et al, 2009;Hong et al, 2009;Kawamura et al, 2009;Li et al, 2009;Marión et al, 2009;Utikal et al, 2009b), chemical compounds that alleviate the stress of DNA damage response may help cells to overcome this barrier. To this end, Vitamin C has been shown to significantly increase the formation of both mouse and human iPSC by suppressing p53 induced cell senescence (Esteban et al, 2010).…”
Section: Chemical Compoundsmentioning
confidence: 99%
“…Thus, overexpression of this TF has profound and lasting consequences on the expression of growth-promoting genes. This process is influenced by the p53 status Kawamura et al, 2009;Mario´n et al, 2009;Utikal et al, 2009).…”
mentioning
confidence: 99%
“…We speculate that p53 or p63 enrichment on myogenin regulatory elements previously observed in non-myogenic cells, such as MEFs, 41 mESC, 42 or primary keratinocytes, 46 may reflect a poised global surveillance system that maintains cell identity and prevents, at least, a myogenic fate transition in response to stress signals. This notion is supported by the observation that elimination of p53 enhances cellular plasticity and efficiency of reprogramming somatic cells to pluripotency 58 and differentiated hepatocytes to malignant cell fates. 59 Intriguingly, under the differentiation condition we observed short-term p53 binding, loss of myogenin repression, and recovery of late-stage differentiation post IR.…”
Section: Discussionmentioning
confidence: 87%